An empirical investigation of the underlying factors of recently declining air pollution in China - Emrah Eray Akça; Tayfun Tuncay Tosun (EQA)
This study analyses the underlying factors of recently declining air pollution in China, utilizing annual time series data from 2000 to 2020 in the autoregressive distributed lag model approach framework. In the empirical setting, air pollution is represented by particulate matter (2.5) concentrations, known as the most detrimental ambient pollutant, and the empirical model includes several socioeconomic potential determinants of air pollution. The main motivation behind this study was the downward trend in air pollution in China as of the second decade of the 2000s. Although it is commonly accepted that the Air Pollution Prevention and Control Action Plan implemented by the Chinese State Council has been effective, the underlying factors of declining air pollution aren’t clear. Based on this motivation, the study revealed the positive impacts of economic growth, industrialization, and foreign direct investment inflows on air pollution. At the same time, medium- and high-tech exports and coal rents are negatively associated with air pollution. In this respect, the overall results particularly emphasize the declining impact of an increase in medium- and high-tech exports on air pollution. In this context, to improve air quality further, the study suggests that China should transform its industrialization structure toward specialization in medium- and high-tech products and promote foreign direct investment inflows specialized in these products. This study provides additional policy recommendations for Chinese policymakers.